Subcutaneous fat necrosis in newborns: a systematic literature review of case reports and model of pathophysiology - Leonie Frank; Stephanie Brandt; Martin Wabitsch (SpringerOpen, 2022)
Abstract Background Subcutaneous fat necrosis of the newborn (SCFN) is a rare disease occurring in the first days of life. Characteristically, the infants show hard nodules in subcutaneous tissue, purple or erythematous in color and appear on the upper back, cheeks, buttocks and limbs. In most cases, SCFN is a self-limiting disease, as the nodules disappear in up to 6 months. A severe complication associated with SCFN is hypercalcaemia. Pathophysiological mechanisms causing SCFN or associated hypercalcaemia are not fully understood yet. Methods A systematic literature research including the six biggest databases for medical research has been used to identify all published case reports of SCFN. N = 206 publications has been identified containing n = 320 case reports. All cases have been classified into four subgroups (depending on reported serum-calcium-level): hypercalcaemia, normocalcaemia, hypocalcaemia or no information given. Reported maternal factors, birth characteristics, details about SCFN, diagnostics, therapy and long-term observations have been extracted from publications. Results This is the first systematic literature research that summed up all published cases of SCFN from 1948 up to 2018. Information about serum calcium level was given in 64.3% of the cases. From those, the majority showed hypercalcaemia (70.5%) (normocalcaemia 25.1%, hypocalcemia 4.3%). 89.3% of newborns with hypercalcaemia showed suppressed levels of the parathormone. Maternal gestational diabetes, maternal hypertensive diseases during pregnancy, macrosomia (> 4000g), asphyxia and therapeutic hypothermia are risk factors for SCFN. Histological findings showed a granulomatous inflammation in 98% of cases. Conclusion We identified that maternal, birth characteristics and therapeutic measures are probably risk factors for SCFN. These risk factors should be taken into account within the care of neonates.